The impact of probable rapid eye movement sleep behavior disorder on Parkinson's disease: A dual-tracer PET imaging study. (February 2022) - Xu, Qian; Jiang, Chengfeng; Ge, Jingjie; Lu, Jiaying; Li, Ling; Yu, Huan; Wu, Jianjun; Wang, Jian; Wu, Ping; Zuo, Chuantao
Abstract: Objective: With a dual-tracer PET study design, this study aimed to identify the differences between PD patients with and without probable RBD (PD+RBD+/PD+RBD-) and the influence of timing of RBD onset [probable RBD anterior to PD onset (PD+RBDa)/probable RBD posterior to PD onset (PD+RBDp)]. Methods: Seventy-four PD+RBD+ patients, sixty-three PD+RBD-patients and twenty healthy controls were enrolled. Clinical variates, striatal DAT tracer uptake, voxel-wise glucose metabolism and Parkinson's disease-related pattern (PDRP) expressions were compared among groups. Results: No significant difference were found on clinical characteristics between PD+RBD+ and PD+RBD-groups. Compared with PD+RBD-group, PD+RBD+ group had more severe dopaminergic dysfunction ( p< 0.05) except for posterior putamen in the more affected hemisphere (MAH) ( p  = 0.350). Meanwhile, it showed relative hypermetabolism in anterior putamen in the less affected hemisphere (LAH), bilateral anterior pallidum with wider involvement in the LAH, hippocampus and para-hippocampus in the LAH and bilateral olfactory gyrus, together with relative hypometabolism in limited bilateral posterio-parietal area ( p< 0.001). Significantly elevated PDRP expression was also seen in PD+RBD+ group ( p  < 0.01). For the timing of RBD onset, PD+RBDa patients harbored greater progression rate than PD+RBDp patients ( p< 0.01), greater DAT declining rates of striatal subregions and greater increasing rate of PDRP expressions than both PD+RBDp and PD+RBD-patients ( p< 0.05). Conclusion: Our study found that PD patients with probable RBD have worse striatal dopaminergic dysfunction and higher PDRP network activity, supporting the assumption that PD with RBD may be a specific phenotype of PD. Additionally, RBD preceding PD onset may indicate a steeper disease decline. Highlights: More severe striatal dopaminergic dysfunction and higher PDRP network activity in PD patients with RBD. RBD happening anterior to PD may accelerate progression rate in early disease stage. Similar imaging progression rate found between PD+RBDp and PD+RBD- groups.